Collocational competence of primary and secondary school students - Miščin Evelina (ExELL (Explorations in English Language and Linguistics))
The aim of the paper is to test collocational competence of primary and secondary school students to establish the most frequent problems they encounter. Based on these collocational errors teachers could devise their teaching material and help students in improving their collocational competence.